Could the CCR5-Delta32 mutation be protective in SARS-CoV-2 infection? - Starcevic Cizmarevic, N; Kapovic, M; Roncevic, D; Ristic, S (Physiological research, 2021)
Increasing evidence points to host genetics as a factor in COVID-19 prevalence and outcome. CCR5 is a receptor for proinflammatory chemokines that are involved in host responses, especially to viruses. The CCR5-delta32 minor allele is an interesting variant, given the role of CCR5 in some viral infections, particularly HIV-1. Recent studies of the impact of CCR5-delta32 on COVID-19 risk and severity have yielded contradictory results. This ecologic study shows that the CCR5-delta32 allelic frequency in a European population was significantly negatively correlated with the number of COVID-19 cases (p=0.035) and deaths (p=0.006) during the second pandemic wave. These results suggest that CCR5-delta32 may be protective against SARS-CoV-2 infection, as it is against HIV infection, and could be predictive of COVID-19 risk and severity. Further studies based on samples from populations of different genetic backgrounds are needed to validate these statistically obtained findings.
Keywords: Genetic Predisposition to Disease; Prevalence; stupeň závažnosti nemoci; ochranné faktory; Europe; SARS-CoV-2; Evropa; prevalence; mutace; COVID-19; fenotyp; Host-Pathogen Interactions; Phenotype; Receptors, CCR5; Mutation; Humans; receptory CCR5; interakce hostitele a patogenu; frekvence genu; rizikové faktory; Gene Frequency; genetická predispozice k nemoci; Risk Factors; Severity of Illness Index; lidé; Protective Factors